Bioengineering of injectable encapsulated aggregates of pluripotent stem cells for therapy of myocardial infarction - Shuting Zhao (Nature Portfolio, 2016)
Stem cell therapy of myocardial infarction is hampered by poor survival of injected cells. Here the authors develop injectable aggregates of stem cells differentiated to an early cardiac stage and encapsulated in a biodegradable micromatrix, and show their enhanced therapeutic efficacy in a heart infarction mouse model.